Mesta in "mala mesta" - Stanič, Ivan (Urbani izziv, 1994)
The hypothesis of the article is, that small towns cannot be defined as a particular category of settlements since the only common denominator between them is the number of their inhabitants. In the explanation former characteristics of towns are discussed, such as the wall, market and statute.
Keywords: mesta; urbana naselja